Effectiveness of a Multidisciplinary Clinical Pathway for Elderly Patients With Hip Fracture: A Multicenter Comparative Cohort Study. (June 2016) - Kalmet, P. H. S.; Koc, B. B.; Hemmes, B.; ten Broeke, R. H. M.; Dekkers, G.; Hustinx, P.; Schotanus, M. G.; Tilman, P.; Janzing, H. M. J.; Verkeyn, J. M. A.; Brink, P. R. G.; Poeze, M.
Introduction: The use of a multidisciplinary clinical pathway (MCP) for patients with hip fracture tends to be more effective than usual care (UC). The aim of this study was to evaluate the effects of an MCP approach on time to surgery, length of stay, postoperative complications, and 30-day mortality, compared to UC. Materials and Methods: This multicenter retrospective cohort study included patients aged 50 years or older with a proximal hip fracture who underwent surgery in one of the 6 hospitals in the Limburg trauma region of the Netherlands in 2012. Data such as demographics, process outcome measures, and clinical outcome were collected. Results: This study included a total of 1193 patients (665 and 528 patients in the MCP and UC groups, respectively). There were no differences in patient demographics present. Time to surgery was significantly shorter in the MCP compared to the UC group (19.2 vs 24.4 hours, P < .01). The mean length of stay was 10 versus 12 days ( P < .01). In the MCP group, significantly lower rates of postoperative complications were observed and significantly more patients were institutionalized than in the UC group. Mortality within 30 days after admission was comparable between the groups (overall mortality 6%). Conclusion: An MCP approach is associated with reduced time to surgery, postoperative complications, and length of stay, without a significant difference in 30-day mortality. The institutionalization rate was significantly higher in the MCP group.